Antioxidant potential and Cancer-specific cytotoxic effect of selected marine microalgal extratcs - Ferdous, Umme Tamanna (2023)
Microalgae derived metabolites have shown potential biological activities, especially antioxidant and cytotoxicity. Marine microalgae are often considered as a mother lode of antioxidant and antitumor compounds due to their inhabitants in the harsh marine environment. Despite having valuable and novel metabolites, the marine microalgae species are still not thoroughly investigated for their pharmaceutical and nutraceutical importance. Since cancer treatment with synthetic drugs shows adverse effects, it is urgent to search for alternative therapy from this promising marine source. Therefore, this study was focused to investigate the crude extracts of six marine microalgae species, Chlorella sp., Tetraselmis sp., Nannochloropsis sp., Isochrysis sp., Chaetoceros sp., and Thalassiosira sp., isolated from Malaysian coastal region in terms of their antioxidant activity and cytotoxicity against human breast cancer cells, MCF-7. These six marine microalgae are considered safe for human and animal usage as well as frequently used as fish feed and dietary supplements. Moreover, microalgae need shorter time, less nutrient and no arable land to grow. These microalgal species were collected and identified based on morphological and molecular characteristics. A total of forty-eight crude extracts from six marine microalgae species were prepared using eight different polarity solvents. From the antioxidant assays, methanol and ethyl acetate extract of Tetraselmis sp. exhibited significantly higher (p<0.05) antioxidant activities, revealed through DPPH (54.41 ± 1.18 mg Trolox Equivalent Antioxidant Capacity or TEAC/g extract) and ABTS (41.57±0.83 mg TEAC/g extract) radical scavenging activities, respectively than the rest. Ethyl acetate extract of Tetraselmis sp. also showed high ferric reducing power (113.46±4.83 mg TEAC/g extract). On the other hand, ethanol extract of Isochrysis sp. reduced the viability of human breast cancer, MCF-7 cells to 7.24 ± 0.47% after 72 hours of incubation, at a concentration of 100 μg/ml. The IC50 (half maximal inhibitory concentration) value was 13.37 ± 0.59 μg/ml after 24 hours in MCF-7 cells and >100 μg/ml in non-cancerous human lung fibroblast cells, MRC-5. Ethanol extract of Isochrysis sp. was further investigated for apoptosis induction in MCF-7 cells. With the increasing concentration of the extract, a reduction in MCF-7 cell population was observed. The Annexin V-FITC and propidium iodide staining analysis confirmed that the mode of cell death is mainly apoptosis. Cell cycle analysis revealed the accumulation of cells in the sub-G0 phase which suggests induction of apoptosis and G2/M cycle arrest. RT-qPCR analysis revealed an up-regulation of the proapoptotic Bax gene and tumor suppressor p53 gene. Metabolite profiling by Liquid Chromatography/Mass Spectrometry showed the presence of possible metabolites from fatty acid, sphingolipid, carotenoid, and phenolic classes. In conclusion, marine microalgae from indigenous sources have shown antioxidant and cancer-selective cytotoxicity. The data suggest that crude ethanolic extract from marine Isochrysis sp. has induced apoptosis and cell cycle arrest in human breast cancer cells, MCF-7, while methanol and ethyl acetate extracts from marine Tetraselmis sp. have good radical scavenging and ferric reduction capability. Therefore, indigenous marine Isochrysis sp. and Tetraselmis sp. may have potential therapeutic value for treating human breast cancer and nutraceutical use, respectively, which needs further investigation along with extensive in vivo study.